Food chemical safety - Watson, D. H. (David H.), 1952- (Woodhead Publishing in food science and technology., 2001)
Chemical contaminants in food, from pesticides and veterinary drug residues to contamination from food packaging, are a major concern for the food industry. Written by a distinguished international team of contributors, this authoritative collection describes the main chemical contaminants, their health implications, how they contaminate food products, methods of detection and how such contaminants can be controlled. Describes the main chemical contaminants of food, their health implications, how they contaminate food products, methods of detection and how such contaminants can be controlled.